HUBUNGAN PAPARAN BENZENE DENGAN FUNGSI PARU PADA AWAK MOBIL TANGKI BBM DI PT. X SEMARANG - Maulina Susilaningtyas; Ari Suwondo; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Benzene is a volatile organic compound (VOC) derived from vehicles, gas station emissions, some industries, cigarette smoke, and some cleaning products. Benzene inhaled can cause irritation to the respiratory tract, symptoms of coughing and tightness. If the concentration of benzene in the air work environment more than the threshold value, it can cause respiratory symptoms resembling acute bronchitis which is characterized by a decrease in pulmonary function. The purpose of this study was to analyze the relationship of benzene exposure to pulmonary function in the Fuel Tank Car Crew (AMT) at PT. X Semarang. This study is an observational study with a cross sectional study design carried out on fuel tank crews. The method used in this study was to measure benzene levels in the air, measurement of phenol levels in urine, measurement of vital lung capacity and interviews with tank crew members. The results of this study were benzene concentration at PT. X is normal <1 ppm with a concentration of 0.013 ppm, 0.004 ppm, and 0.000 ppm. Workers who have phenol levels in urine> 25 ppm as much as 80.6%, as many as 61.3% are active smokers, 51.6% of workers experience decreased lung function, as many as 67.7% of workers aged> 30 years, as many as 48.4 % of workers had worked for> 5 years, 45.2% of workers did not exercise regularly, 61.3% of workers had risky nutritional status, and 29% of workers had low oxygen saturation. The results of the relationship test of 6 variables showed there was a relationship between age, smoking habits, and exercise habits with lung vital capacity. Based on the Prevalence Ratio value, low oxygen saturation is 1,901 times the risk of causing lung vital capacity disruption.